SAT0374 Do Patients with Non-Radiographic Axial Spondyloarthritis and Ankylosing Spondylitis Respond Similarly Well to Nsaids? A Prospective Study Including Magnetic Resonance Imaging. (10th June 2014) - Baraliakos, X.; Kiltz, U.; Heldmann, F.; Appel, H.; Dybowski, F.; Igelmann, M.; Kalthoff, L.; Krause, D.; Menne, H.-J.; Saracbasi, E.; Schmitz-Bortz, E.; Braun, J.
Abstract : Background: Patients classified as axial spondyloarthritis (axSpA) may have ankylosing spondylitis (AS) or non-radiographic axSpA (nr-axSpA). Treatment recommendations for AS consider non-steroidal anti-inflammatory drugs (NSAIDs) as first-line therapy. After an unsatisfactory response to at least 2 non-steroidal anti-inflammatory drugs (NSAIDs) within 4 weeks (wk), anti-TNF agents are to be considered. However, it is unknown whether patients with nr-axSpA and AS respond similarly well to NSAIDs. Methods: Consecutive patients (pts) with axSpA (n=50 with nr-axSpA and n=50 with AS) were included in a prospective study if their BASDAI level was ≥4, if they had not yet received the maximally approved dose of NSAIDs and if they had not been treated with anti-TNF agents to date. After inclusion the maximal dose of NSAIDs was administered over 1wk and the dose was then adapted in case of BASDAI <4 or, in case of BASDAI ≥4, the NSAID was changed and the pt was treated for another 3 wk at the maximal dose. Clinical and laboratory parameters and dosage of drugs were assessed by using the ASAS NSAID-index. Magnetic resonance images (MRI) of the sacroiliac joints including STIR sequences were performed and scored by the Berlin score. Data were collected before (BL) and after 1 and 4 wk of treatment. Results: nr-axSpA pts were more often female than AS pts (52% vs. 70%), were younger (mean age 37.6±11 vs. 41.9±12.3 years), and had a shorter symptom duration (7.3±9.1 vs. 14.6±11.837.6±11 years) but were similarly often HLA-B27+ (74% vs. 80%), all p=n.s. Significant differences between the groups were found in mean CRP levels (0.6±0.9 vs. 1.2±1.1) and mean MRI scores (3.1±3.0 vs. 6.7±5.4) in nr-axSpA vs. AS pts, respectively, both p<0.001. Prior to treatment, the ASDAS-CRP was >2.1 in 76% and 74% and a positive MRI occurred in 70% and 78% of pts with nr-axSpA and AS, respectively. After wk1 and wk4, both groups showed similarly increased rates in the NSAID-index and also similar responses to NSAIDs, with significant improvement from BL in all assessments with the exception of CRP levels and MRI-a scores, where almost no changes were observed. At wks 1 and 4, an ASAS20% response was found in 40% (21% with nr-axSpA and 19% with AS) and in 52% of pts (23% nr-axSpA and 29% AS), while ASAS partial remission was found in 10% (4% nr-axSpA and 6% AS) and in 16% of pts (7% nr-axSpA and 9% AS), respectively. However, 49% and 44% of all pts still had a BASDAI ≥4 at wks 1 and 4, and similar results were found for an ASDAS-CRP cut-off of ≥2.1, with 37% and 33% achieving this at wks 1 and 4 (no differences between nr-axSpA and AS). Conclusions: Patients with nr-axSpA and AS show similar response rates to NSAID treatment. Although there was some improvement of ASAS response rates, 40-50% of pts with axSpA still showed BASDAI levels >4 after 4wk of intensive NSAID therapy and were, thus, eligible for anti-TNF therapy. Bone marrow edema on MRI and CRP levels were not influenced by continuous NSAID treatment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6085